The Future of Human Health, Longevity, and Health Costs - Sebastian Böhm; Volker Grossmann; Holger Strulik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We investigate the future of human longevity, morbidity and health costs in a novel, multi-period OLG model with endogenous medical R&D and endogenous survival. Our calibrated model implies substantial future increases in longevity that are associated with both reductions in morbidity and a rising health expenditure share in GDP. Extending health care rationing has potentially sizable effects on morbidity and longevity, with dramatic welfare losses particularly for future generations.
Keywords: H50; 330